A Comparison of Iron and Folate with Folate Alone in Hematologic Recovery of Children Treated for Acute Malaria - Gara, Samuel N. (The American Society of Tropical Medicine and Hygiene, 2010)
Concern has been raised that iron supplementation for treatment of acute malaria may worsen the severity of malaria. We compared the effect of iron and folate with folate alone on hematologic recovery in children treated for acute malaria. We randomized 82 children 6–60 months of age from Nigeria with smear-positive malaria and anemia (hematocrit < 33%) to receive iron (2 mg/kg/day) plus folate (5 mg/day) or folate alone in addition to antimalarial drugs. The mean ± SD hematocrit at baseline was 28.5% ± 2.9%. At four weeks, the mean hematocrit increased by 2.5% ± 1.6% in the iron plus folate group and by 1.4% ± 1.0% in the folate alone group (P = 0.001). Baseline hematocrit, iron supplementation, weight for height, and weekly meat intake were significant predictors of final hematocrit. The effect of iron was not significantly modified by baseline hematocrit, weekly meat intake, nutritional status, mother's education, sex, or age of the child. Iron supplementation improved hematologic recovery in children with malarial anemia.